2009
DOI: 10.1016/j.jcmg.2008.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Spectroscopy in Myocardial Disease

Abstract: Magnetic resonance spectroscopy (MRS) is the only noninvasive, nonradiation exposure technique for the investigation of cardiac metabolism in vivo. MRS uses magnetic resonance signals from nuclei, such as (31)phosphorus, (1)hydrogen, and (23)sodium, to provide comprehensive metabolic and biochemical information about cardiac muscle. This method is highly versatile and can provide metabolic insights into the role of cardiac metabolism, in particular, cardiac energetics, in a wide number of conditions, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 64 publications
1
58
0
1
Order By: Relevance
“…31 Phophorus magnetic resonance spectroscopy studies performed in patients with advanced LV failure have repeatedly demonstrated decreased myocardial levels of creatine and ATP and correlations between these levels and survival. 99 …”
Section: Molecular and Perfusion Imaging Magnetic Resonance Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…31 Phophorus magnetic resonance spectroscopy studies performed in patients with advanced LV failure have repeatedly demonstrated decreased myocardial levels of creatine and ATP and correlations between these levels and survival. 99 …”
Section: Molecular and Perfusion Imaging Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…128 During the process of apoptosis, the phospholipid phosphatidylserine is expressed on the outer cell membrane and serves as a signal for cell removal by macrophages. 129 Annexin is a protein that binds to phosphatidylserine, and single-photon emission computed tomography imaging showed increased 99 Tc-labeled annexin V uptake in the failing LV 130 and in rejected cardiac transplants. 131 Similar results were obtained in PH animal models, but these data have not yet been confirmed in patients with PAH.…”
Section: Rv Apoptosismentioning
confidence: 99%
“…5 Although this technique is currently limited to a substantial extent with regard to determination of energetic status during stress and also imposes substantial limits of spatial resolution within the myocardium, it represents a means to obtain additional insights into the relationships between hemodynamic, autocoidal, and genetic stimuli and the development of left ventricular hypertrophy, myocardial metabolic efficiency, and cardiac function. In this regard, a number of recent publications have documented that left ventricular hypertrophy in general is associated with decreased PCr:ATP ratios, 6 whereas systolic heart failure, irrespective of the presence or absence of underlying large-vessel coronary artery disease, is also associated with impaired energetics.…”
Section: Hcm and Impaired Myocardial Energeticsmentioning
confidence: 99%
“…7 Although cardiac proton MRS studies offer tremendous potential for clinical and research applications, the technique remains challenging to perform and interpret. 8 Furthermore, as opposed to MRI-based techniques such as late gadolinium enhancement, no clinical question has been identified that cardiac MRS can uniquely answer to affect patient treatment, limiting its widespread adaptation. This is in contrast to the research applications of proton MRS to assess myocardial lipid or phosphorus MRS to quantify cardiac high-energy phosphates.…”
Section: Article See P 710mentioning
confidence: 99%